2023
DOI: 10.1038/s41467-023-40913-7
|View full text |Cite
|
Sign up to set email alerts
|

A versatile, fast and unbiased method for estimation of gene-by-environment interaction effects on biobank-scale datasets

Matteo Di Scipio,
Mohammad Khan,
Shihong Mao
et al.

Abstract: Identification of gene-by-environment interactions (GxE) is crucial to understand the interplay of environmental effects on complex traits. However, current methods evaluating GxE on biobank-scale datasets have limitations. We introduce MonsterLM, a multiple linear regression method that does not rely on model specification and provides unbiased estimates of variance explained by GxE. We demonstrate robustness of MonsterLM through comprehensive genome-wide simulations using real genetic data from 325,989 indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…First, we distinguish three different types of GxE interaction: Imperfect genetic correlation, Varying genetic variance, and Proportional amplification (Figure 1a; also see Supplementary Figure 6). Second, most variance components methods for detecting genome-wide GxE [13][14][15]17,18 cannot detect genome-wide GxE unless SNP-heritability varies across E bins (Scenario 2). An exception is GxEMM 16 , which detects other types of GxE by explicitly modeling genetic and environmental variance that varies with the E variable; however, GxEMM is less computationally tractable and generally less powerful than our framework (Supplementary Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we distinguish three different types of GxE interaction: Imperfect genetic correlation, Varying genetic variance, and Proportional amplification (Figure 1a; also see Supplementary Figure 6). Second, most variance components methods for detecting genome-wide GxE [13][14][15]17,18 cannot detect genome-wide GxE unless SNP-heritability varies across E bins (Scenario 2). An exception is GxEMM 16 , which detects other types of GxE by explicitly modeling genetic and environmental variance that varies with the E variable; however, GxEMM is less computationally tractable and generally less powerful than our framework (Supplementary Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have detected GxE at a limited number of specific loci [5][6][7] (including studies that associated genotype to phenotypic variance without knowing the underlying E variable [8][9][10][11][12] ). Previous studies have also proposed variance components methods for detecting genome-wide contributions of GxE to disease heritability [13][14][15][16][17][18] , but these methods have not been applied at biobank scale across a broad range of disease/traits. Thus, the overall contribution of GxE to disease/trait architectures is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To analyze binary outcomes, we transformed the observed-scale heritability to liability-scale heritability using Roberston transformation 18 . It has been pointed out that when the GE interaction variance is large, the normality assumption of the phenotype liability may be violated, resulting in biased results of Roberston transformation 8,38 . However, our simulation results showed that when the GE interaction variance proportion was small Roberston transformation still yielded reasonably accurate result (S Figure 1, S Table 1), consistent with previous studies 8 .…”
Section: Methodsmentioning
confidence: 99%
“…Broad-scale sequencing of wild populations Many computational methods available (e.g., GREML Yang et al, 2015;Di Scipio et al, 2023), which can parse genetic, environmental and their interaction using SNP matrices.…”
Section: Reciprocal Common Gardensmentioning
confidence: 99%